Effects of Predator’s Consumption on Crop-Pest-Predator Models subject to Pest Harvesting with Bifurcation Analysis - Liu, Qiu Yan; Mohd Safuan, Hamizah (Enhanced Knowledge in Sciences and Technology, 2025)
Mathematical modelling translates real-world scenarios into mathematical expressions, such as equations, to represent the dynamics of a system. This approach enhances the accuracy of predictions regarding system behaviour. In this study, ecological model consists of crop, pest, and predator populations is utilised to examine how dynamic interactions impact ecosystem stability. The model considers pests consuming crops and predators preying on pests. This study focuses on the dynamics of a crop-pest-predator system which utilises two ecological models, one with and one without pest harvesting control. The consumption rate of pests by predators serves as the main bifurcation parameter, and both models are analysed to determine their respective dynamics. The stability of steady states and equilibrium points is evaluated in each model through numerical and Bifurcation analysis. Numerical and graphical analyses are applied to explore the effects of varying consumption rates of pests on the dynamics and stability of the system. Excessive rate of consumption rates of pests by predators may lead to oscillatory dynamics. The model with the pest harvesting control demonstrates a broader range of stability, highlighting its potential to enhance the stability of the ecological system. However, the findings also highlight the importance of maintaining balance, as excessive control measures can disrupt the ecosystem’s equilibrium. These insights contribute to the development of more effective and resilient agricultural systems that optimise the pest management strategies.